До питання про чинники дітородної активності населення - Крімер, Б.О. (Інститут демографії та соціальних досліджень НАН України, 2010)
Стаття присвячена дослідженню чинників народжуваності в сучасних умовах. Розглядаються теорії, що пояснюють зниження народжуваності в нинішніх умовах, та аналізується рівень і характер впливу на неї окремих суспільно-економічних чинників. На цій основі проводиться ранжування країн Європи за ступенем сприятливості суспільно-економічного середовища для народження дитини. Статья посвящена исследованию факторов рождаемости в современных условиях. Рассмотрены теории, которые дают объяснение снижению рождаемости в современных условиях. Также анализируется уровень и характер влияния на рождаемость отдельных социально-экономических факторов. На этой основе страны Европы ранжируются по уровню благоприятности общественно-экономичской среды для рождения ребенка. The determinants of fertility in modern environment are analyzed in this paper. The different theories of fertility are characterized. The most influential following determinants of fertility are considered: family income end economic environment, womens employment, womens education, family policy, religiosity, marital status. The levels of influence of social-economic determinants are estimated. Family income and employment are most important determinants, but their impact is not absolute. The impact of major determinants of fertility over the past decade were changed. On this basis a friendliness of social environment for childbearing was estimated. The place of Ukraine among European countries in friendliness of social environment for childbearing are allocated. This place is one of the last in Europe.